Kebijakan Anti-Riba di Turki: Tinjauan Konsep Al-Ḥisbah Dalam Kebijakan Ekonomi Recep Tayyip Erdoğan - Fajar Satriyawan Wahyudi; Muhammad Azrul Amirullah; Meitria Cahyani (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2025)
The anti-usury policy promoted by Turkish President Recep Tayyip Erdoğan, through the emphasis on low interest rates, is one effort to implement sharia principles in the modern macroeconomic system. This policy aligns with the concept of Al-Hisbah, which in the history of the Islamic State successfully eradicated usury and created economic welfare and prosperity. However, its implementation in the modern era faces serious and complex challenges, such as high inflation, the depreciation of the lira exchange rate, and resistance from the business community and investors. This study aims to analyze the gap between the practice of Al-Hisbah in the past and its current implementation, focusing on Erdoğan's economic policies. Using a qualitative approach and descriptive analysis, this study examines historical literature and economic data on Erdoğan's policies. The results show that although Erdoğan's anti-usury policy is firmly grounded in sharia principles, its implementation is still constrained by the global economic system that has integrated interest rates into its practice, making it very difficult for a country to break out of this cycle. Thus, a holistic and context-based approach is needed to ensure that anti-riba policies not only create economic benefits but also minimize the potential for mafsadah (harmful acts). Furthermore, this policy can serve as a strategic model for other Muslim countries in building consensus to reform the capitalist system toward an economic order more aligned with Islamic principles